FAKTOR RISIKO ANEMIA IBU HAMIL DI INDONESIA - Tanziha, Ikeu; Damanik, Muhammad Rizal Martua; Utama, Lalu Juntra; Rosmiati, Risti (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
The objective of the study was to analyze the risk factors for anemia among pregnant women in Indonesia. The study design was a cross-sectional study. All of data used in this study was from Basic Health Research 2013, Ministry of Health. The data collected include age, education, birth number, parity, pregnancy spacing, antenatal care, and nutritional status (chronic energy deficiency). The number of subjects was 452 pregnant women. The chi-square test was applied to analyze correlation on dependent and independent variable. Logistic regression was applied to analyze determinants of anemia in pregnant women. The results showed that there were 38.1% pregnant women in Indonesia who had anemia (Hb<11 g/dl). The prevalence of pregnant women with anemia in rural and urban were 37.9% and 38.2% respectively. Bivariate analysis showed that age, education, birth number, parity, pregnancy spacing, and antenatal care were not significantly associated with anemia. Main determinant of anemia in pregnant women was nutritional status (chronic energy deficiency; OR=1.975; 95%CI:1.279-3.049).